An Exciting New Development in Hydrometallurgical Reserach-The A J Parker Cooperative Research Centre for Hydrometallurgy (The Australasian Institute of Mining and Metallurgy, 1992)
The A J Parker Cooperative Research Centre for Hydrometallurgy has recently been established by a major grant from the Australian Commonwealth Government. The participating institutions in this centre are the CSIRO Division of Mineral Products, Curtin University of Technology, Murdoch University and the Chemistry Centre (WA). The Australian Mineral Industries Research Association is also a partner. Information is presented about the research activities of the Parker Centre, which are focussed on the solid/solution interface. Three research programs have been established in the areas of leaching, precipitation and surface processes (adsorption). The initial projects within these three programs are described. Details are also given of the Centre's education program which include honours degree training, masters and doctoral degrees by research, a masters degree by course work and workshops. The importance of collaboration with industry to the successful operation of the centre is stressed.